Positive and linear association of hepatic steatosis index with female infertility in US women: results from the National Health and Nutrition Examination Survey 2013–2018 - Wu, Xinjie; Zhang, Lin; Wu, Weihua (Frontiers in Public Health, 2025)
BackgroundFemale infertility is a global reproductive health challenge. The hepatic steatosis index (HSI) is a simple and non-invasive screening tool for steatosis. We herein explore the association of HSI with female infertility through the National Health and Nutrition Examination Survey (NHANES) 2013–2018.MethodsThis cross-sectional study included 2,133 reproductive-age women from 15 U.S. states, with data collected through standardized questionnaires, physical examinations, and laboratory tests across three survey cycles (2013–2018). HSI was assessed based on body mass index, ALT/AST, sex, and diabetes status. Female infertility status was ascertained through standardized questionnaire items reflecting clinical diagnostic criteria (≥1 year of unprotected intercourse without conception), though not verified by medical records or fertility testing. Multivariable logistic regression analysis was used to explore the association between HSI and female infertility and to calculate the odds ratio (OR) and 95% confidence interval (CI). Restricted cubic spline (RCS) and stratified analyses were further employed to examine potential nonlinear relationships and subgroup disparities. Explored the factors affecting HSI through multivariate analysis.ResultsA total of 2,133 reproductive-age women were enrolled, of whom 271 had infertility. There was no significant trend in HSI levels across cycles. In the fully adjusted model, HSI showed positive cross-sectional associations with self-reported infertility status (OR 1.02, 95% CI 1.01–1.04, p = 0.005). Compared to Q1, HSI at Q4 was associated with a 72% increase in the odds of female infertility (p = 0.003). Restricted cubic spline (RCS) analysis indicated that this association was linear (p for nonlinear = 0.9698). Stratified analyses suggested that this association was more pronounced among those <35 years of age and those with <high school education. RCS analyses based on age subgroups similarly indicated that this association was significant and linear among participants <35 years.ConclusionHSI was positively associated with the odds of female infertility and demonstrated a linear dose–response association. These findings suggest that HSI may be used as an potential marker to screen reproductive age women at high risk of infertility, although further research is needed to validate its predictive utility and clinical applicability.